Acquisition of 3D models with submillimeter-sized features from SEM images by use of photogrammetry: A dimensional comparison to microtomography. (June 2019) - Barbieri, Gabriel; da Silva, Fabio Pinto
Highlights: In the present study, a specimen was rotated automatically inside the SEM chamber to obtain 3D meshes. Meshes obtained from different sides of a specimen were merged into a single closed 3D model. This study compared SEM-photogrammetry to microtomography and evaluated the quantitative accuracy of a 3D model. Abstract: The use of three-dimensional models for analysis has been increasing in various fields. This study aimed to analyze the process of acquiring 3D meshes by photogrammetry using scanning electron microscopy (SEM) images. 3D models were reconstructed from different numbers of SEM images using a free photogrammetry software. The 3D models obtained were aligned and compared quantitatively to a model obtained by microtomography (microCT). The results suggest that it is possible to reconstruct 3D photogrammetric models with micrometric precision using SEM. However, the error depends on the number of images used for 3D reconstruction (and on the rotation angle). The best result obtained by photogrammetry at 9° step showed a percentage error of 0.3%. The worst result (27°) had a 1.4% error compared to those obtained by microCT. SEM photogrammetry is capable of providing surface details almost as accurate as microCT and therefore, it can be an interesting alternative for the analysis of external surfaces.